Detecting Vibrations produced by faults in a wheel of a pedal cycle through Continuous Wavelet Transform and calculations - et. al., Ravikumar. K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper is about the fault detection based on wheels in a pedal cycle which is detected using vibrations. These vibration signals are analysed by wavelet analysis. The faults arise in wheels are puncture, chain break, brake rub, hub squeak, cracked rim, cracked tyre, tread worn off, loose joints and bearing fault. We shall study how these vibrations caused by the faults look like in wavelet analysis. We use Continuous Wavelet Transform (CWT) to analyse the vibration.